Preparation and layer-by-layer solution deposition of Cu(In,Ga)O2 nanoparticles with conversion to Cu(In,Ga)S2 films. - Walter J Dressick; Carissa M Soto; Jake Fontana; Colin C Baker; Jason D Myers; Jesse A Frantz; Woohong Kim (PLoS ONE, 2014)
We present a method of Cu(In,Ga)S2 (CIGS) thin film formation via conversion of layer-by-layer (LbL) assembled Cu-In-Ga oxide (CIGO) nanoparticles and polyelectrolytes. CIGO nanoparticles were created via a novel flame-spray pyrolysis method using metal nitrate precursors, subsequently coated with polyallylamine (PAH), and dispersed in aqueous solution. Multilayer films were assembled by alternately dipping quartz, Si, and/or Mo substrates into a solution of either polydopamine (PDA) or polystyrenesulfonate (PSS) and then in the CIGO-PAH dispersion to fabricate films as thick as 1-2 microns. PSS/CIGO-PAH films were found to be inadequate due to weak adhesion to the Si and Mo substrates, excessive particle diffusion during sulfurization, and mechanical softness ill-suited to further processing. PDA/CIGO-PAH films, in contrast, were more mechanically robust and more tolerant of high temperature processing. After LbL deposition, films were oxidized to remove polymer and sulfurized at high temperature under flowing hydrogen sulfide to convert CIGO to CIGS. Complete film conversion from the oxide to the sulfide is confirmed by X-ray diffraction characterization.